PREDIKSI KEBANGKRUTAN PT GARUDA INDONESIA TBK PERIODE 2020–2024 DENGAN METODE ALTMAN Z-SCORE MODIFIKASI, SPRINGATE, DAN GROVER - Yulyanah yulyanah (Universitas Logistik dan Bisnis Internasional, 2026)
This study aims to analyze the accuracy and relevance of three bankruptcy prediction models—namely the Modified Altman Z-Score, Springate, and Grover—in predicting financial distress in the airline sector, specifically at PT. Garuda Indonesia (Persero) Tbk. The research employs a qualitative approach using secondary data from financial statements. The three prediction models were applied to assess the company's financial condition on an annual basis, with the final category determined based on the average score. The results indicate that all three models consistently predicted that PT. Garuda Indonesia Tbk was in a state of bankruptcy throughout the observation period. Although a temporary improvement was observed in 2022, this was reflected in working capital, low retained earnings accumulation, and poor profitability. These findings confirm that the three bankruptcy prediction models remain relevant and provide strong early warning signals for management, investors, and creditors to take corrective actions. This study is expected to serve as a reference for internal and external decision-makers and to support efforts in anticipating bankruptcy risks in the aviation industry.